Liver Pathology Associated With Natural Infection of Schistosoma Incognitum in Slaughtered Pigs - Sethi, Menaka; Das, Tareni; John, Jeny K; Sreelekshmy Mohandas; Banerjee, Partha Sarathi; Singh , Rajendra; Guttula Saikumar (International Journal of Livestock Research, 2018)
Schistosomiasis is a wide-spread chronic helminthic infection which contributes to death of over half a million people yearly. It is a significant cause of morbidity and mortality. Pork is the world’s most consumed meat. Liver the rich source of protein and is edible offal. The present study was conducted to study liver pathology and diagnosis of causative agents associated with the lesions in slaughtered house collected samples. During the study period, (100) liver samples showing gross pathological alterations were collected from pigs slaughtered in Bareilly, UP. The samples were fixed in 10% buffered neutral formalin and processed for histopathological examination. Out of 100 liver samples, Schistosoma incognitum was detected in 5 liver tissue sections. Histopathological examination revealed granuloma of liver which consists of epithelioid cells, macrophages, giant cells, eosinophils, lymphocytes and plasma cells with (and) small lymphoid nodules. On Masson’s trichrome staining, fibrous tissue proliferation was demonstrated in periductal region around egg and adult male of Schistosoma incognitum. The Schistosoma species was identified by observing typical short stout sub terminal spine in eggs found in the liver granuloma.